PENGARUH KUALITAS PELAYANAN, LOKASI DAN HARGA TERHADAP MINAT BELI ULANG, MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO AIR MINERAL PRIM-A DI SITUBONDO - Stefania Goreti Bata; Hendra Syahputra; Mohammad Yahya Arief (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to investigate the effect of service quality, location, and price on repurchase intention, with customer satisfaction serving as an intervening variable, at the Prim-A Mineral Water Store in Situbondo, Indonesia. The study population consists of customers of the Prim-A store. A simple random sampling technique was employed, resulting in 98 valid respondents included in the data analysis. Data analysis and hypothesis testing in this study were conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis testing using the PLS 3.0 application indicate the following: Service quality has a negative and insignificant effect on customer satisfaction at the Prim-A mineral water store in Situbondo Regency. Location also shows a negative but insignificant effect on customer satisfaction. Price has a significant positive effect on customer satisfaction. Service quality has a significant negative effect on repurchase intention. Location has a negative but insignificant effect on repurchase intention. Price shows a positive but insignificant effect on repurchase intention. Customer satisfaction has a significant positive effect on repurchase intention. Additionally, service quality has a negative but insignificant effect on repurchase intention; location has a negative but insignificant effect on repurchase intention; and price has a significant positive effect on repurchase intention.